2000
DOI: 10.1007/s11745-000-0651-6
|View full text |Cite
|
Sign up to set email alerts
|

Effect of medium‐chain fatty acid positional distribution in dietary triacylglycerol on lymphatic lipid transport and chylomicron composition in rats

Abstract: The present study was carried out to examine if the positional distribution of medium-chain fatty acid (MCF) in dietary synthetic fat influences lymphatic transport of dietary fat and the chemical composition of chylomicrons in rats with permanent cannulation of thoracic duct. Four types of synthetic triacylglycerol were prepared: (i) sn-1 (3) MCF-sn 2 linoleic acid, (ii) interesterified sn-1(3) MCF-sn 2 linoleic acid, (iii) sn-2 MCF-sn-1(3) linoleic acid, and (iv) interesterified sn-2 MCF-sn-1(3) linoleic aci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0
2

Year Published

2001
2001
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 34 publications
0
18
0
2
Order By: Relevance
“…44 Furthermore, esterified FA10:0 found in the plasma may also be contributed by chylomicrons, since possible integration of dietary MCFA into chylomicrons cannot be excluded. [45][46][47][48][49] Nonetheless, these MCFA-containing triglyceride-rich lipoproteins can be important substrates for lipoprotein lipase in the capillaries of adipose tissues, skeleton, and cardiac muscles. The MCFA that are taken up by adipose tissues can be stored and subsequently released into the circulation, depending upon the feed/fast cycle.…”
Section: Esterified Capric Acid Concentrationmentioning
confidence: 99%
“…44 Furthermore, esterified FA10:0 found in the plasma may also be contributed by chylomicrons, since possible integration of dietary MCFA into chylomicrons cannot be excluded. [45][46][47][48][49] Nonetheless, these MCFA-containing triglyceride-rich lipoproteins can be important substrates for lipoprotein lipase in the capillaries of adipose tissues, skeleton, and cardiac muscles. The MCFA that are taken up by adipose tissues can be stored and subsequently released into the circulation, depending upon the feed/fast cycle.…”
Section: Esterified Capric Acid Concentrationmentioning
confidence: 99%
“…The two lipids are differently transported in the body, MCT is directly transported by the portal blood to the systemic circulation , whereas LCT is transported in the intestinal lymphatics. However, some of the medium-chain saturated fatty acids are resynthesized or re-esterified to triacylglycerols or neutral lipids, packaged within apoprotein surface layers and transported via the lymphatic system (Green & Glickman, 1981;Ikeda et al, 1991;Carvajal et al, 2000;Mu & Hoy, 2001;Holm et al, 2002). Recently, Sun et al (2011) have reported that, the lymphatic transport of sirolimus from SMEDDS formulation containing !25% MCT was a major contributor to its oral bioavailability.…”
Section: Introductionmentioning
confidence: 99%
“…However, molecular-level effects of TAG with similar FA compositions but different positional distributions of FA have previously been compared in the rat model only. In these studies MCFA have been absorbed via the portal venous system as well as incorporated into chylomicron TAG (2)(3)(4)(5). The proportion of MCFA incorporated into chylomicrons has depended on the position of the MCFA in the TAG molecule (2,6), and the overall lymph flow or TAG output has (7) or has not (5) been affected by the location of the MCFA.…”
mentioning
confidence: 99%